2013
DOI: 10.4161/viru.27393
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnosis of sepsis

Abstract: Fast and appropriate therapy is the cornerstone in the therapy of sepsis. However, the discrimination of sepsis from non-infectious causes of inflammation may be difficult. Biomarkers have been suggested to aid physicians in this decision. There is currently no biochemical technique available which alone allows a rapid and reliable discrimination between sepsis and non-infectious inflammation. Procalcitonin (PCT) is currently the most investigated biomarker for this purpose. C-reactive protein and interleukin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(128 citation statements)
references
References 98 publications
3
116
1
8
Order By: Relevance
“…Compared to CRP or PCT, IL-6 levels peak 2 h after initiation of the inflammatory cascade. Based on this rapid increase, IL-6 was introduced as a biomarker of early sepsis in emergency units [38,39] . A multicenter study showed that IL-6 can predict survival on the 28 th day after sepsis onset [40] .…”
Section: Il-6mentioning
confidence: 99%
“…Compared to CRP or PCT, IL-6 levels peak 2 h after initiation of the inflammatory cascade. Based on this rapid increase, IL-6 was introduced as a biomarker of early sepsis in emergency units [38,39] . A multicenter study showed that IL-6 can predict survival on the 28 th day after sepsis onset [40] .…”
Section: Il-6mentioning
confidence: 99%
“…However, biomarkers can aid and shorten this decision process when taking into account the shortcomings of biomarkers. Procalcitonin is currently the most investigated biomarker for this purpose and the only biomarker which has been integrated into treatment algorithms 14 . Recently, the biomarkers used as diagnostic criteria for sepsis, plasma CRP or PCT levels more than 2 standard deviations (SD) above the normal value, are now part of the inflammatory variables which, together with infection, whether documented or suspected, constitute a definition of sepsis 6,15 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted on the differential diagnosis of sepsis and NI-SIRS in recent years have focused on the indicators which yield results more rapidly in the early period. Among them, clinical scoring systems such as the SOFA and immunological markers such as procalcitonin and sTREM-1 are the leading ones (3,7,13).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, laboratory investigations yielding rapid and accurate results to support the diagnosis are needed. Blood culture growth, the differential diagnosis criterion, cannot be achieved in all patients, and the results cannot be obtained earlier than 24 h. On the other hand, when attempting to confirm the absence of infection in patients suspected to have sepsis but in fact not having sepsis, serious diagnostic problems arise (3).…”
Section: Introductionmentioning
confidence: 99%